Converging fate of the oxidation and reduction of 8-thioguanosine - Taras Goslinska, Katarzyna (2019)
Thione-containing nucleobases have attracted the attention of the scientific community for their application in oncology, virology, and transplantology. The detailed understanding of the reactivity of the purine derivative 8-thioguanosine (8-TG) with reactive oxygen species (ROS) and free radicals is crucial for its biological relevance. An extensive investigation on the fate of 8-TG under both reductive and oxidative conditions is here reported, and it was tested by employing steady-state photooxidation, laser flash photolysis, as well as γ-radiolysis in aqueous solutions. The characterization of the 8-TG T1 excited state by laser flash photolysis and the photooxidation experiments confirmed that singlet oxygen is a crucial intermediate in the formation of the unexpected reduced product guanosine, without the formation of the usual oxygenated sulfinic or sulfonic acids. Furthermore, a thorough screening of different radiolytic conditions upon γ-radiation afforded the reduced product. These results were rationalized by performing control experiments in the predominant presence of each reactive species formed by radiolysis of water, and the mechanistic pathway scenario was postulated on these bases.